The Effectiveness of the Dictogloss Technique in Teaching Narrative Text Writing (An Experimental Study in Class IX of SMP Parulian 3 Medan) - Rohana Engelis Estomihi Sinaga; Rahmawati Rahmawati; Mayasari Mayasari (RIRAI Publisher, 2024)
This study aims to elucidate the empirical findings of the effectiveness of dictogloss approaches in teaching grade IX students at SMP Parulian 3 Medan how to create narratives. This study uses a quantitative approach. Pretest and posttest design is the experimental methodology used in this study. 36 students in grade IX at SMP Parulian 3 Medan participated in the study's population during the 2023–2024 academic year. The researcher chose two groups as the research sample by using purposive sampling. Class IX A, an experimental class, and class IX B, a control class that will learn to produce narrative texts using dictogloss procedures, make up the chosen research sample class. There were 36 pupils between the two classes. Before therapy, the researcher administered a pretest to both classes, and following treatment, a posttest. Students are instructed to produce narrative texts for both the pretest and posttest using the writing instrument used in this study. The efficacy of the dictogloss technique on students' narrative text writing was then ascertained by utilizing the t test formula to examine the data collected from the pretest and posttest. The t-observation value was 4.27 in the results. The tt (ttable) value with 34 degrees of freedom at a significance degree of 5% is 2.03. This shows that t is greater than tt, or alternative hypotheses (H_o) are rejected, and the alternative The hypothesis (H_a) is agreed upon. Thus, it can be said that the scores of students' narrative writing before and after using the dictogloss technique differ significantly. Stated differently, the dictogloss technique is effective for learning to write narrative texts.